Normalisation comptable et nouvelles technologies - Côté, Yves-Aubert; Lequin, Yves (Assurances)

(untitled) (HEC Montréal, 1994)
A trendy phenomenon in a world dominated by an economic pseudo-rationality or a new, accidental and destabilizing phenomenon whose consequences are beyond our control — such is the perception of the omnipresent introduction of new technologies into industrial economies at the end of this century. The accounting disciplines, the crossroads for information passing through and surrounding a company, cannot ignore the emergence of these challenges. In the following study, the authors first define the expression "new technologies" and then analyze the various sources and effects of accounting standardization to more clearly define the possible consequences of this new phenomenon for accounting and certification professionals.